Association of Inflow Cannula Position with Left Ventricular Unloading and Clinical Outcomes in Patients with HeartMate II Left Ventricular Assist Device. Issue 4 (May 2019) - Imamura, Teruhiko; Nguyen, Ann; Chung, Ben; Rodgers, Daniel; Sarswat, Nitasha; Kim, Gene; Raikhelkar, Jayant; Adatya, Sirtaz; Ota, Takeyoshi; Song, Tae; Juricek, Colleen; Estep, Jerry D.; et al.
Abstract : The relationship between the HeartMate II left ventricular assist device (LVAD) position and pump thrombosis has been reported. However, further clinical implications of device position are unknown. This study aimed to investigate optimal device position for better left ventricular (LV) unloading and patient prognosis. Patients undergoing a ramp test with right heart catheterization after HeartMate II LVAD implantation were enrolled to this study. Device position was quantified from the chest X-ray obtained at the time of the ramp test: (1) inflow cannula angle relative to horizontal line, (2) pump angle relative to spine, (3) pump depth, (4) angle between inflow cannula and pump, and (5) angle between pump and outflow graft. LV unloading was assessed by pulmonary capillary wedge pressure at set LVAD speed. Fifty-four patients (60 years old and 34 male [63%]) were enrolled. Nobody experienced device malfunction during the study period. Increased LV unloading ( i.e., lower pulmonary capillary wedge pressure) was associated with a narrower inflow cannula angle relative to horizontal line. Inflow cannula angle <75° was associated with higher 1 year heart failure readmission-free survival rate ( p < 0.05, hazards ratio 7.56 [95% confidence interval 2.32–24.7]). In conclusion, HeartMate II LVAD inflow cannula position was associated with LV unloading and patient prognosis. Prospective studies to ensure optimal device positioning and target better clinical outcomes are warranted. Abstract : Supplemental Digital Content is available in the text.